EFISIENSI USAHATANI PAKCOY (Brassica rapa L.) DI DESA BATUNYA KECAMATAN BATURITI KABUPATEN TABANAN - Yohana Lanung; I Ketut Arnawa; Ni Putu Sukanteri; Ida Ayu Made Dwi Susanti (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
This research aims to i) analyze production costs, income, feasibility of pak-coy farming, (ii) identify obstacles in pak-coy farming in Batunya Village, Baturiti District, Tabanan Regency. The technique for taking respondents was carried out using the census method, totaling 30 people. The research results show that the production cost per season of Pakcoy farming is IDR 32,366,993.00 per hectare. Income of IDR 77,503,974.00 per hectare. Feasibility of farming with an R/C ratio value of 3.39, which means that pak choy farming is feasible to develop. Internal obstacles in farming are limited farming capital, not calculating costs, expenses or income, difficulty in getting subsidized urea fertilizer, lack of labor during processing and harvesting, pest attacks in the rainy season. Meanwhile, external obstacles consist of: lots of competition from outside the village, higher risk of crop failure in the rainy season, no business partnerships and lack of agricultural technology